'Happy Children'A project that has the aim of developing emotional literacy and conflict resolution skills. A Maltese Case Study. (2nd January 2021) - Bezzina, Amanda; Camilleri, Stephen
ABSTRACT: 'Happy Children' was launched as part of the Friendship Cards initiative. FC is an educational tool that was developed by Relationships are Forever Foundation (RAFF), in collaboration with various professionals coming from the field of education and counselling. This study examines the effects of the use of FC interactive tool on children's social-emotional competence. It is a theoretically derived preventive programme that helps students develop their social and emotional understanding so that they are able to manage their feelings and deal with conflicts in a positive way. FC serve as a springboard for lessons on emotional understanding, expression and management, perspective taking, reflection on one's actions and conflict management and resilience. The study included a thematic analysis of the reflections elicited from 80 reflective journals presented by educators, counsellors, psychologists and social workers who attended specific training on the use of this tool. The reflective journals had the intention of helping participants in the study to reflect on the outcomes of their activities, using FC. Results from this study indicate that the tool enhances the social and emotional learning of children and adolescents in a fun and experiential way. The tool enhances reflection, thinking and analysis of one's emotions and behaviour. www.friendshipcards.org